Leverage Points and Cascading Impacts Analysis in Nexus Systems Using System Dynamics Modeling - Virginia R. Coletta; Irene Pluchinotta; Vassilios Pisinaras; Andreas Panagopoulos; Raffaele Giordano; Alessandro Pagano; Umberto Fratino; Alberto Montanari (Earth's Future)
Abstract Operationalizing the Water‐Ecosystem‐Food (WEF) Nexus approach for sustainable resource management is challenging due to the complexity, non‐linearity, and uncertainty of interconnected resources systems. A promising strategy requires identifying leverage points, namely key elements and processes where interventions can generate significant systemic change. However, leverage points are often difficult to discover and typically treated as static nodes rather than evolving and uncertain. To overcome this gap, qualitative and quantitative System Dynamics modeling tools are combined with other system‐analysis methods. Unlike traditional approaches, the proposed modeling framework analyses leverage points as key dynamic elements, links, and feedback loops that activate and shift in intensity based on system state. The modeling process, applied to the Pinios River Basin (PRB) in Greece, helped revealing critical leverage points, including factors such as groundwater quality and agricultural productivity, key causal influences like the impact of natural areas' condition on agrotourism, and relevant feedback loops, such as the reinforcing dynamic driving the decline of natural areas. Deterministic and stochastic simulations contributed to validate the robustness of the modeling framework, with stochastic methods providing additional insights into the variability and uncertainty of system behavior. Recurring leverage points across simulations proved essential to drive effective management during critical transitions. Beyond the PRB, this modeling process provides a versatile framework for understanding and managing complex multi‐sector systems, applicable to different contexts to support strategic decision‐making toward sustainability and cascading impacts mitigation.